Inducible NO synthase expression is low in airway epithelium from young children with cystic fibrosis. Issue 6 (3rd March 2006) - Moeller, A; Horak, F; Lane, C; Knight, D; Kicic, A; Brennan, S; Franklin, P; Terpolilli, J; Wildhaber, J H; Stick, S M
Abstract : Background: This is the first study to measure inducible nitric oxide synthase (iNOS) gene and protein expression quantitatively in primary epithelial cells from very young children with cystic fibrosis (CF). Low levels of exhaled nitric oxide (NO) in CF suggest dysregulation of NO production in the airway. Due to the importance of NO in cell homeostasis and innate immunity, any defect in the pathway associated with CF would be a potential target for treatment. Methods: Cells were obtained by tracheobronchial brushing from 40 children with CF of mean (SD) age 2.1 (1.5) years and from 12 healthy non-atopic children aged 3.4 (1.2) years. Expression of iNOS mRNA was measured using quantitative PCR and iNOS protein by immunofluorescence and Western blot analysis. Results: Inducible NOS mRNA expression was significantly lower in CF patients with and without bacterial infection than in healthy children (0.22 and 0.23 v 0.76; p = 0.002 and p = 0.01, respectively). Low levels of iNOS gene expression were accompanied by low levels of iNOS protein expression as detected by Western blot analysis. Conclusions: These results support the findings of previous studies in adult patients with advanced disease, cell lines, and animal models. Our findings reflect the situation in children with mild lung disease. They indicate that low iNOS expression may be an innate defect in CF with potential consequences for local antimicrobial defence and epithelial cell function and provide evidence for an approach to treatment based on increasing epithelial NO production or the sensitivity of NO dependent cellular processes.